Evaluación de Genotipos de tomate (Lycopersicon esculentum Mill) tolerantes al estrés hídrico en Manglaralto, Cantón Santa Elena, Provincia de Santa Elena. - Tomalá Flores, Segundo Antonio (2017)
The present study dealt with the evaluation of water stress tolerant tomato genotypes in Manglaralto, Santa Elena canton, province of Santa Elena, whose objective was to evaluate 675 tomato genotypes, tolerant to water stress, the work was done on the Campus of Practices of the UPSE, located in the parish Manglaralto, the used statistic was Distribution of Frequencies and histograms of frequencies; In addition, a simple linear regression analysis. To verify tolerance to water stress, tomato genotypes, the SEPOR (2010) methodology was used. Based on this model, a liter of water was applied in a period of 30 minutes to all genotypes including the control, throughout the vegetative cycle of the plants, starting from the transplant; until the beginning of the first harvest. The management of the test was done by imitating the farmer, except for the phytosanitary control, which was carried out in an ecological way. The variables evaluated were: germination percentage, plant height, flowering day, crop day, pest incidence, number of fruits per plant, weight of plant fruits and Brix grades. The results showed that the best genotypes selected from the Acerado hybrid were: 1, 5, 6, 7, 11, 28; for their flowering days from 37 to 48, days at harvest from 91 to 101 days, plant height from 84 to 93 cm, number of fruits from 8 to 10, fruit weight from 67 to 77 grams and brix degrees from 5.1 to 5.2. According to the polynomial regression, the selected genotypes have been shown to be resistant, because they received a liter of water every day from the transplant to the filling of the fruit, during which time they were subjected to the aforementioned stress.